Die missionere gerigtheid van die kerk - Merwe, J. C. van der (Hervormde teologiese studies, 1997)
The church as missionary church. Statistics show that the Nederduitsch Hervormde Kerk van Afrika is not growing. The basic cause of this situation seems to be that the Church is not spending enough of its efforts and energy on being a missionary church, but on maintaining itself. The negative tendencies of the institutional and the preaching models seem to previal. This study is an attempt to show that church-method and being-church are indissolubly tied to each other. Being-church means, in the light of this study, being God's missionary in the worldfor the glory of God - being a missionary church.